Hubungan Pengetahuan Dengan Kepatuhan Santriwati Dalam Menerapkan Protokol Kesehatan Covid-19 Pada Era New Normal - Tirta Amerta Isworo; Mila Sri Lestari; Gufron Wahyudi (Institut Nalanda, 2024)
This study aims to determine whether there is a relationship between Knowledge and Santriwati Compliance in Implementing COVID-19 Health Protocols in the New Normal Era at the Darussalam Islamic Boarding School Blokagung Banyuwangi. Quantitative research method, for sampling methods in this study using the type of probability sampling with simple random sampling techniques. The data were analyzed using Pearson Correlation analysis. It was found that students' knowledge of covid-19 health protocols was included in the good category (66.21%), and for students' compliance in implementing covid-19 health protocols was in the good category (65.43%). There is a significant relationship between knowledge and student compliance in implementing COVID-19 health protocols in the new normal era at the Darussalam Islamic Boarding School Blokagung Banyuwangi with a P-Value value of 0.000 and a correlation coefficient value of -0.507.